Modified Minimally Invasive Ilioinguinal approach to the Acetabulum Fracture - Leuva, Hemant; Patel, Nimish; Parmar, K D (International Journal of Medical Research and Review, 2014)
Introduction: The ilioinguinal approach is the most commonly utilized approach for fixing fractures of the acetabulum. Letournel et al described the classical ilioinguinal approach in 1960 and it has been in use for fixation of a subset of acetabular fractures since long. Methods: We present a minimally invasive modification of the same approach in which fixation is carried out using only two windows as compared to the classic three window approach. The modified minimally invasive approach was used to fix 12 patients of fracture acetabulum requiring anterior exposure during a one year period starting from 1 Jan 2012 to 31 Dec 2012. The iliac vessels and nerves are protected thereby requiring no preparation of the neurovascular bundle. Result: There were no incidences of vascular injury or inguinal hernias. None of the patients had implant failure or surgery for removal of implants. As compared to the classical ilioinguinal approach there was less time required for exposure. Conclusion: The classical ilioinguinal approach and its various extensile approaches have been used to improve direct visualization and reduction of acetabulum fractures. In many of the fractures the complete exposure is not required for accurate reduction and fixation which has led to the development of newer less invasive approaches. The modified minimally invasive ilioinguinal approach can be used to fix most of the simple fractures.